Adrift in a Sea of Information about Sustainable Seafood: The Maine Consumer Perspective - Schmitt, Catherine (Maine Policy Review, 2011)
The desire for a sustainable seafood industry that protects the environment and the future of fishing is certainly of interest to consumers, but even here there are conflicting standards, as Catherine Schmitt explores in this article.